Corrosion Behavior of Ni3(Si,Ti) + 2Mo in Hydrochloric Acid Solution - Gadang Priyotomo; Pius Sebleku (International Journal of Science and Engineering, 2014)
The corrosion behavior of Ni3(Si,Ti) + 2Mo intermetallic compound (L12 and (L12 + Niss) mixture region) has been investigated using an immersion test, polarization method and surface analytical method (scanning electron microscope and energy-dispersive X-Ray spectrometry) in 0.5 kmol/m3 hydrochloric acid (HCl) solution at 303 K.  In addition, the results obtained were compared to those of the L12 single-phase Ni3(Si,Ti) intermetallic compound and C 276 alloy.  It was found that Ni3(Si,Ti) + 2Mo had the preferential dissolution of L12 with a lower Mo concentration compared to (L12 + Niss) mixture region.  From the immersion test and polarization curves, Ni3(Si,Ti) + 2Mo and C276 showed the lowest corrosion resistance and the highest corrosion resistance in the solution, respectively.  From this work, It implied that unlike C276, Ni3(Si,Ti) +2Mo intermetallic compound was difficult to form a stable passive film in HCl solution as well as Ni3(Si,Ti) in the same solution.